The motive behind international diversification acquisition by business group - Edi, Edi; Tilani, Agnes; Karjantoro, Handoko (Business: Theory and Practice, 2024)
This study aims to determine the influence of the industry group business on international acquisition diversification with private ownership and strategic asset seeking as moderating variables. Using resource-based and institutional theory, this study hypothesizes that the industry group business provides benefits and encourages diversification of international acquisitions. In addition, this study also argues that private ownership and strategic assets seeking amplify the influence of industry group business on diversification international acquisition. The novelty of this research aims to address by proposing strategic assets seeking as a moderated variable that influence industry group business on diversified international acquisitions. The sample data of this research are companies listed on the Indonesia Stock Exchange between 2018–2021. The findings of this research can be useful for companies to understand the significance of intangible assets and how they can leverage them to gain a competitive advantage in their respective industries. The results of this study will greatly assist researchers in the field of international acquisitions.